Effectiveness of In-House Training in Improving The Knowledge of Prospective Brides in Conducting The Eight Family Functions of Marriage - Farida Ariyani; Widya Lestari; Dian Febrida Sari; Mel Sofia Ananda; Resi Gusrita Dwi Putri (Jurnal Kesehatan dr. Soebandi, 2025)
The strategy that can be used to realize the goals of marriage and family is to increase family resilience. If family resilience weakens, conflict will arise in the household. The increase in divorce cases in the last six years has reached 516,334. Family conditions that experience conflict and even divorce have implications for the health of each individual in the family. This study focuses on the method of modifying the guidance of prospective brides and grooms. They must follow In House Training through an application that contains information about reproductive health, eight family functions, family resilience and stunting prevention. The purpose of this study was to determine the effectiveness of In House Training on increasing the knowledge and readiness of prospective brides and grooms in carrying out family functions. This study used a quasi-experimental method with a pre-experimental design with a One-Group Pre-Posttest Design approach. The research sample was prospective brides and grooms who would get married in the next 2-3 months, with a purposive sampling method of 22 people. The variables in this study were the knowledge of prospective brides and grooms about the eight family functions. The statistical test used in this study was the Wilcoxon Test. This study was conducted for one year. The results showed that there was a difference in knowledge before and after the infusion training intervention was given to prospective brides and grooms with a Z value of 0.000. Research can be conducted on both prospective brides and grooms about their readiness to carry out the eight family functions